2003
DOI: 10.1177/0013164402250988
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Predictors Of The Propensity To Omit Short-Response Items On A High-Stakes Achievement Test

Abstract: This article presents the findings of a study of the psychological variables that discriminate between high and low omitters on a high-stakes achievement test using a short-response format. Data were obtained from a questionnaire administered to a random sample ( N = 1,908) of students prior to sitting the 1997 Queensland Core Skills (QCS) Test ( N = 29,273). Fourteen psychological variables were measured including test anxiety (four subscales), emotional stability, achievement motivation, self-esteem, academi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…In the present study, female students scored statistically significantly higher than male students on the TAICA Total Test Anxiety scale and a composite variable consisting of the scores from the four debilitating test anxiety subscales. These results are in agreement with the gender differences reported in the literature, with female participants scoring statistically significantly higher than male participants on self-report measures of test anxiety (e.g., Gierl & Rogers, 1996;Matters & Burnett, 2003;Seipp & Schwarzer, 1996). Findings from meta-analytic studies have found a modest relationship between test anxiety and gender, with female students scoring higher than male students by approximately a third of a standard deviation (Hembree, 1988;Seipp & Schwarzer, 1996).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, female students scored statistically significantly higher than male students on the TAICA Total Test Anxiety scale and a composite variable consisting of the scores from the four debilitating test anxiety subscales. These results are in agreement with the gender differences reported in the literature, with female participants scoring statistically significantly higher than male participants on self-report measures of test anxiety (e.g., Gierl & Rogers, 1996;Matters & Burnett, 2003;Seipp & Schwarzer, 1996). Findings from meta-analytic studies have found a modest relationship between test anxiety and gender, with female students scoring higher than male students by approximately a third of a standard deviation (Hembree, 1988;Seipp & Schwarzer, 1996).…”
Section: Discussionsupporting
confidence: 90%
“…Grandy (1987) found that omissions in the General Record Examination are affected by students’ ability, sex, age, ethnicity, and the educational background of their parents. Matters and Burnett (2003) investigated relationships between the tendency to omit short-response items and psychological factors using data from the Queensland Cores Skills Test. They found that students were more likely to omit items when they had lower academic self-concept, self-estimate of ability, and motivation for achievement and higher test-irrelevant thoughts to interfere with performance.…”
Section: Tendency To Omit Itemsmentioning
confidence: 99%
“…So far, studies have shown rather inconsistent results regarding different missing data approaches and estimated latent ability variances, reporting overestimation, underestimation, or no bias at all (Custer et al., ; Rose, ; Rose et al., ). Regarding explanatory variables and interest in their relationship with competence, it is also noteworthy that omitted and not‐reached items typically relate to potential explanatory variables such as gender, ethnicity, and other competences (Köhler, Pohl, & Carstensen, ; Koretz, Lewis, Skewes‐Cox, & Burstein, ; Matters & Burnett, ). Glas, Pimentel, and Lamers () investigated the impact of explanatory variables that correlate with missing propensity and competence on the estimation of item difficulty parameters.…”
mentioning
confidence: 99%